Avaliação da força muscular, capacidade pulmonar e capacidade ao exercício dos candidatos ao transplante de fígado acompanhados no ambulatório de um hospital universitário. - Almeida, Marley Cintra de [UNIFESP] (2018)
Due to the changes caused by terminal liver disease, patients on the waiting list for liver transplantation may present decreased muscle strength, altered lung capacity, and poor exercise capacity. essential factors in order to design effective and satisfactory strategies in pre-transplant physiotherapeutic care. Objectives: To evaluate muscle strength, lung capacity and exercise capacity of patients candidates for liver transplantation and to correlate with their clinical variables. Methods: The patients enrolled in the single technical registry for liver transplants of the Federal University of São Paulo, from February 2015 to February 2016, of both sexes and aged 18 years or over, were evaluated. Muscle strength was assessed by measuring Manual Grip Strength, lung capacity through Slow Vital Capacity and Respiratory Pressures, and ability to exercise through the 6-minute walk test. Results: The sample consisted of 50 patients, 62% of whom were males, with a mean age of 52.2 ± 12.6 years. The mean Slow Capacity was 72.8 ± 22.7% of predicted value (p <0.001). In the 6 'walk test, the mean was 76.6 ± 15.4% of predicted (p <0.001). Maximum inspiratory pressure was 26.5 ± 9.9% predicted (p <0.001), Maximum Expiratory Pressure reached 32 ± 11.7% of predicted (p <0.001), and the Manual Holding Force reached totaled 119 ± 28.8% of predicted. Fatigue and absence of regular physical activity were factors that negatively influenced the Maximum Inspiratory Pressure values (p <0.001). Patients who had ascites, fatigue or did not practice regular physical activity obtained worse performance in the Manual Grip test (p <0.005). Conclusion: Respiratory muscle strength, slow vital capacity, and ability to exercise are significantly reduced in patients who are candidates for liver transplantation. Fatigue, ascites and lack of regular physical activity were factors that negatively influenced the results of Maximum Inspiratory Pressure and Manual Grip Strength.